KINERJA GURU YANG TELAH LULUS SERTIFIKASI GURU DALAM JABATAN - Universitas Veteran Bangun Nusantara Sukoharjo, Soebagyo Brotosedjati (Jurnal Manajemen Pendidikan, 2012)
Abstract: The Performance of Teachers Who Have Passed the Teacherâs Certification in Functional. This study aims to obtain and examine the existence of differences in teacher performance after obtaining a certificate of educators in Central Java. The method of this study combines the quantitative and qualitative research methods with a model of naturalistic and phenomenological approach. Data obtained from 1.540 respondents from 20 different schools range from TK/RA (kindergartens) to public or private SMA/SMK (high schools or vocational high schools). Conclusion (1) Certification has been improving the welfare, dignity, discipline and pedagogical competence of the teachers, (2) Certification through PLPG have a higher capacity than through the PSPL and PSPF, and (3) there is a significant relationship between the high age and educational level with the proportion of certification completion. Â Abstrak: Kinerja Guru yang Telah Lulus Sertifikasi Guru dalam Jabatan. Penelitian ini bertujuan untuk memperoleh gambaran dan menguji ada tidaknya perbedaan kinerja guru setelah memperoleh sertifikat pendidik di Jawa Tengah. Metode Penelitian ini menggabungkan metode penelitian kuantitatif dan kwalitatif dengan model naturalistik dan pendekatan fenomenologis. Data diperoleh dari 1.540 responden berasal dari 20 jenis sekolah TK/RA sampai SMA/SMK Negeri maupun swasta. Simpulan (1) Sertifikasi telah meningkatkan kesejahteraan, martabat, kedisiplinan dan kompetensi pedagogis, (2) Sertifikasi melalui PLPG mempunyai kemampuan lebih tinggi dibanding dengan melalui PSPL dan PSPF, dan (3) ada hubungan yang signifikan antara Strata Pendidikan dan usia yang tinggi dengan proporsi kelulusan sertifikasi. Â Keywords: performance, teacher, certification.